Hubungan Pola Asuh Otoriter dengan Kemandirian Anak Usia Dini di Jorong Atas Mesjid Bukit Sileh Kabupaten Solok - Silpasari Silpasari; Ismaniar Ismaniar (Program Studi PGRA, 2020)
This research is motivated by the low independence of early childhood as evidenced by the ability of children to carry out their activities. It is suspected that the low development of aspects of children's independence is caused by many factors. One of them is parenting patterns that are not appropriate. This study aims to look at the description of parental authoritarian parenting, a description of the independence of early childhood, the relationship of authoritarian parenting with the independence of early childhood in Jorong Atas Mesjid Bukit Sileh, Solok Regency. This research is a descriptive correlational research population taken from parents who have early childhood. The sampling technique used was stratified cluster random sampling. The sample was taken as much as 75% of the total population of 50 people, 37 people. Techniques and tools to collect data using a questionnaire technique with data analysis using the percentage formula and product moment.The results showed that the description of parental care of children in the Jorong Atas Mesjid Bukit Sileh,Solok regency applied a very authoritarian parenting pattern, a picture of the independence of early childhood in Jorong Atas Mesjid Bukit Sileh, Solok Regency, classified as less independent, and there was a significant relationship between patterns authoritarian fostering with the independence of early childhood.